The Correlation Analysis Between m6A Methylation Modification and Ferroptosis Induced by Cigarette Smoke in Human Bronchial Epithelium - Xiaomei Duan; Tingting Hu; Lijuan Xu; Zheng Li; Jing Jing; Dan Xu; Jianbing Ding; Fengsen Li; Min Jiang; Jing Wang (Immunity, Inflammation and Disease)
ABSTRACT Background Chronic obstructive pulmonary disease (COPD), a prevalent respiratory condition, is characterized by long‐term airway inflammation, which can lead to airway remodeling and persistent airflow restriction. Exposure to cigarette smoke is known as a major contributor to COPD development. Research has confirmed that ferroptosis and m6A modification are closely related to various inflammatory‐related diseases. However, the correlation between m6A methylation and ferroptosis in COPD has not been confirmed. In this study, combined with bioinformatics analysis and molecular biology methods we investigated how m6A methylation was correlated to ferroptosis‐associated genes (SLC7A11 and NQO‐1) in cigarette smoke induced 16HBES cells. Methods Two microarray datasets (GSE30063 and GSE64614) were combined to identify differentially expressed genes (DEGs) through the application of bioinformatics techniques. A cigarette smoke (CS)‐induced 16HBE cells model was established. The ROS, GSH, MDA, and total iron content were detected by relevant detection kits. The expression levels associated with ferroptosis and m6A methylation modification‐related genes were determined via reverse transcription‐quantitative polymerase chain reaction and western blot. Results Overall, 529 DEGs were identified in the above two databases. For COPD patients, significant changes were observed in FAGs (GCLC, NQO‐1, SLC7A11) and m6A methylation‐related genes (FTO). A negative correlation was also noted between the expression level of genes linked to ferroptosis (SLC7A11 and NQO‐1) and that of the m6A methylation gene (FTO). The in vitro experiments results indicate that SLC7A11 and NQO‐1 were significantly downregulated, and FTO were significantly upregulated. In addition, cigarette smoke stimulation increased the levels of MDA, LPO, and ROS, while reducing the content of GSH and total iron content in 16HBE cells. Conclusion Our findings explored the relationship between ferroptosis and m6A methylation in COPD, and screened out SLC7A11, NQO‐1 and FTO may be critical in the pathogenesis of COPD.